1947
DOI: 10.1002/jez.1401040105
|View full text |Cite
|
Sign up to set email alerts
|

Regression and shortening of the primitive streak in the explanted chick blastoderm

Abstract: Since the time of Dursy (1866) who first extensively investigated the development of the primitive streak in the chick, embryologists have been interested in the manner of origin and growth in length of the streak and its relationship to the developing embryo. The recent experiments of TVillier and his students on blastoderms of the head-process and definitive primitive streak stages have shown that many organforming areas have a definite spatial arrangement about the anterior end of the streak (see Willier an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

1957
1957
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(39 citation statements)
references
References 16 publications
2
34
0
3
Order By: Relevance
“…Fates of mesoderm precursors in the primitive streak vary depending on the stages. Generally speaking, posterior part (1/2 to 1/3) of the primitive streak continues to give rise to extraembryonic fated mesoderm from HH2 to at least HH9 (Murray, 1932;Nakazawa et al, 2006;Nocolet, 1970;Peebles, 1898;Psychoyos and Stern, 1996;Rawles, 1936;Rosenquist, 1966;Rudnick, 1938;Sawada and Aoyama, 1999;Schoenwolf et al, 1992;Spratt, 1942;Spratt, 1946;Spratt, 1947;Spratt and Haas, 1965). Relative to more axially located mesoderm lineages (the axial, paraxial, intermediate and lateral plate mesoderm), extraembryonic mesoderm precursors are of the ventralmost fate and populate the lateralmost regions of the developing embryo.…”
Section: Extraembryonic Mesoderm and Ventral Mesodermmentioning
confidence: 99%
“…Fates of mesoderm precursors in the primitive streak vary depending on the stages. Generally speaking, posterior part (1/2 to 1/3) of the primitive streak continues to give rise to extraembryonic fated mesoderm from HH2 to at least HH9 (Murray, 1932;Nakazawa et al, 2006;Nocolet, 1970;Peebles, 1898;Psychoyos and Stern, 1996;Rawles, 1936;Rosenquist, 1966;Rudnick, 1938;Sawada and Aoyama, 1999;Schoenwolf et al, 1992;Spratt, 1942;Spratt, 1946;Spratt, 1947;Spratt and Haas, 1965). Relative to more axially located mesoderm lineages (the axial, paraxial, intermediate and lateral plate mesoderm), extraembryonic mesoderm precursors are of the ventralmost fate and populate the lateralmost regions of the developing embryo.…”
Section: Extraembryonic Mesoderm and Ventral Mesodermmentioning
confidence: 99%
“…3). Results of earlier mapping studies 56 suggested that the prospective neuroectoderm is organized in a linear, craniocaudal sequence, so that prospective forebrain cells are located more cranially than prospective midbrain cells. In more recent studies, however, a different organization is suggested.…”
Section: Localization Of Prospective Neuroectodermmentioning
confidence: 99%
“…In the chick, the notochordal process grows largely by the latter mechanism. 56 In mammals, analysis of the available evidence suggests that the situation is much more complex and may involve both mechanisms. 60 The mechanism of notochord elongation in humans is unknown.…”
Section: Regression Of the Primitive Streak And Formation Of The Notomentioning
confidence: 99%
“…Two hundred forty-seven dozen embryos were used in the pharmacological study, 15 dozen and 9 dozen for the determination of the amount of CAMP and calmodulin, respectively, in the neural tube during occlusion. The embryos were excised from the yolks, the vitelline membrane was removed, and the embryos were aseptically transferred to small Petri dishes containing either modified Spratt agar substrate (Spratt, 1947) or liquid medium (physiological saline, Hank's salt, or medium 199).…”
Section: Experimental Procedures Culture Conditions and Assessment Ofmentioning
confidence: 99%